KEPENTINGAN PALESTINA BERGABUNG SEBAGAI ANGGOTA MAHKAMAH PIDANA INTERNASIONAL - Ulfa, Nadiyati; Saeri, Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This thesis discusses Palestine's interest in joining the International Criminal Court. The obstruction of peace negotiations between Palestine and Israel for decades has led to the final decision on the borders of the two countries between Palestine and Israel has not been reached. It is getting worse because the military attacks launched by Israel in the Palestinian territories are included in war crimes, crimes against humanity, crimes of genocide, and crimes of aggression. Based on this situation, Palestine made accession to the Rome Statute to join the International Criminal Court. The research method used is a qualitative method with data collection techniques through literature studies. This research uses the Neorealism perspective to explain the international structure acts as a controller of state behavior, so that state policies are within the scope expected by the system. International Law Theory is used to analyze how the International Criminal Court deals with the Israeli-Palestinian conflict. The concept of national interest is used to analyze Palestinian actions when joining the International Criminal Court. The results showed that Palestine gained an increase in statehood status and changed the attitude of the International Criminal Court towards Israel. The real form is that Palestine has now been recognized as a state and Israeli state leaders and war leaders have been summoned to the International Criminal Court for trial Keywords: National Interest, Conflict, International Criminal Court, Rome Statute